Clinicopathologic and Genomic Landscape of Breast Carcinoma Brain Metastases. (23rd June 2021) - Huang, Richard S.P.; Haberberger, James; McGregor, Kimberly; Mata, Douglas A.; Decker, Brennan; Hiemenz, Matthew C.; Lechpammer, Mirna; Danziger, Natalie; Schiavone, Kelsie; Creeden, James; Graf, Ryon P.; Strowd, Roy; et al.
Abstract: Background: Among patients with breast carcinoma who have metastatic disease, 15%–30% will eventually develop brain metastases. We examined the genomic landscape of a large cohort of patients with breast carcinoma brain metastases (BCBMs) and compared it with a cohort of patients with primary breast carcinomas (BCs). Material and Methods: We retrospectively analyzed 733 BCBMs tested with comprehensive genomic profiling (CGP) and compared them with 10, 772 primary breast carcinomas (not-paired) specimens. For a subset of 16 triple-negative breast carcinoma (TNBC)–brain metastasis samples, programmed death-ligand 1 (PD-L1) immunohistochemistry (IHC) was performed concurrently. Results: A total of 733 consecutive BCBMs were analyzed. Compared with primary BCs, BCBMs were enriched for genomic alterations in TP53 (72.0%, 528/733), ERBB2 (25.6%, 188/733), RAD21 (14.1%, 103/733), NF1 (9.0%, 66/733), BRCA1 (7.8%, 57/733), and ESR1 (6.3%, 46/733) ( p < .05 for all comparisons). Immune checkpoint inhibitor biomarkers such as high tumor mutational burden (TMB-high; 16.2%, 119/733); high microsatellite instability (1.9%, 14/733); CD274 amplification (3.6%, 27/733); and apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like mutational signature (5.9%, 43/733) were significantly higher in the BCBM cohort compared with the primary BC cohort ( p < .05 for all comparisons). When using both CGP and PD-L1 IHC, 37.5% (6/16) of patients with TNBC brain metastasis were eligible for atezolizumab based on PD-L1 IHC, and 18.8% (3/16) were eligible for pembrolizumab based on TMB-high status. Conclusion: We found a high prevalence of clinically relevant genomic alterations in patients with BCBM, suggesting that tissue acquisition (surgery) and/or cerebrospinal fluid for CGP in addition to CGP of the primary tumor may be clinically warranted. Implications for Practice: This study found a high prevalence of clinically relevant genomic alterations in patients with breast carcinoma brain metastasis (BCBM), suggesting that tissue acquisition (surgery) and/or cerebrospinal fluid for comprehensive genomic profiling (CGP) in addition to CGP of the primary tumor may be clinically warranted. In addition, this study identified higher positive rates for FDA-approved immunotherapy biomarkers detected by CGP in patients with BCBM, opening a possibility of new on-label treatments. Last, this study noted limited correlation between tumor mutational burden and PD-L1 immunohistochemistry (IHC), which shows the importance of testing patients with triple-negative BCBM for immune checkpoint inhibitor eligibility with both PD-L1 IHC and CGP. Abstract : This article examines the genomic landscape of breast cancer brain metastasis samples with comprehensive genomic profiling in a large cohort of patients to define the potential applicability of recent therapeutic advances.